Hope, Perceived Financial Risk and Propensity for Indebtedness - Lucia Barros; Delane Botelho (BAR: Brazilian Administration Review, 2012)
Hope is an important construct in marketing, since it is an antecedent of important marketing variables, such as trust, expectation and satisfaction (MacInnis & Mello, 2005). Specifically, literature suggests that hope plays an important influence in risk perception (MacInnis & Mello, 2005) and propensity for indebtedness (Fleming, 2008). Thus, we aim to investigate the relationships among hope, risk perception related to purchasing and consumption and propensity for indebtedness by conducting two empirical studies. The first is a laboratory experiment, which accessed hope and risk perception of getting a mortgage loan. The second is a survey, investigating university students’ propensity to get indebted to pay for their university tuition, analyzed through the Structural Equations Modeling method. These studies found that higher levels of hope predicted an increase in the propensity to accept the mortgage loan, independent of actual risks, and an increase in the propensity of college students to get indebted to pay for their studies. In addition, the first study suggests that hope may lead to a decrease in risk perception, which, however, wasn’t confirmed by the second study. Finally, this research offers some methodological contributions, using an experimental approach to understand hope and its relationship with perceived financial risk and propensity for indebtedness.